Monitoring flexicurity policies in Europe from three different viewpoints - Andranik Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2006)
The notion of flexicurity promotes the idea of compensation of labour market deregulation (= flexibilization) with advantages in employment and social security. To monitor effects of flexicurity policies in Europe, flexicurity indicators are constructed. The European flexicurity polices are analyzed in the neo-liberal perspective, from the trade-unionist viewpoint, and within the conception of European welfare state. The empirical investigation shows that, contrary to political promises and theoretical considerations, the deregulation of European labour markets is absolutely predominating. To surmount this policy contradiction, a so called flexinsurance is proposed, meaning that the employer's contribution to social security should be proportional to the flexibility of the contract/risk of becoming unemployed.
Keywords: J65; J26; J21; C51; C43; 330; flexicurity; labour market flexibility; social security; composite indicators